Effects of Water on Hydrophobization and Mechanical Properties of Thermoplastic Agar. Issue 1 (March 2021) - Agusman,; Fransiska, D; Nurhayati,; Irianto, H E; Priambudi, P; Abdullah, A H D; Nissa, R C; Asri, P P P; Masruchin, N; Sedayu, B B; Hakim, A R; Wullandari, P; et al.
Abstract: Thermoplastic agar (TPA) was prepared by a melt extrusion process and the effects of water contents on the material properties of these foams were investigated. Bioplastics were produced by mixing agar, glycerol, and water at ratio agar; glycerol: water was 5:3:2; 5:3:3; and 5:3:4 through the melting process at 120 °C and 18 rpm. The addition of water affected the extrusion process more easily, so the pellet could move easily from the extruder, but the moisture content of TPA increased with water addition. Then, TGA analysis showed no difference in decreasing mass in the sample with water addition. Permeability, elongation, contact angle, density, moisture content, and WVTR of bioplastics increased with water addition. The FTIR curves indicated that the interaction between water and agar may form much more hydrogen bonds. The best treatment was bioplastics with agar:glycerol:water=5:3:2, which have characteristics: tensile strength 16.19 MPa, elongation at break 102.56%, moisture content %, contact angle 72.81°, density 1.38 g/ml, moisture content 3.09%, transparency value 0.067, and WVTR 1334.59 g/m2.24 h.